Hepatitis C virus infection and oral lichen planus: A controversial association - Salma Adnane; Chaimaa Mahad; Sofia Haitami; Ihsane Ben Yahya (Elsevier, 2022)
Oral lichen planus (OLP) is a chronic inflammatory dermatosis that affects the mucous membrane of the oral cavity. Its clinical aspects are polymorphic.In 2016, the disease was organized into six subtypes, according to its clinical expression; erosive, plaque type, papular, reticular, atrophic, and bullous form. Although the disorder may occur in all age groups, women over the age 50 years are most commonly affected.The cause of lichen planus is not completely understood, but genetics and immunity may be involved. Many reports have suggested the association of OLP and HCV infection. However, studies carried out around the world concluded to conflicting results.In this article, we report some cases of patients with oral lichen planus and with a history of recently cured viral hepatitis C, treated at the Oral Surgery Department of the Dental Consultation and Treatment Center of Casablanca and we searched the literature concerning this association to better understand its physiopathological mechanisms.